Hepatoprotective effect of protocatechuic acid against type 2 diabetes-induced liver injury - Kaixia Xu; Guang Lu; Qianjin Feng; Shuangchao Chen; Yonghui Wang (Taylor & Francis Group, 2023)
AbstractContext Protocatechuic acid (PCA) has a protective effect on alcoholic liver injury, but the role of PCA in type 2 diabetes-induced liver injury is not well known.Objectives This study explores the therapeutic effect and potential mechanism of PCA on type 2 diabetes-induced liver injury.Materials and methods An insulin resistance/type 2 diabetic (IR/D) model was established by high-fat diet for 4 weeks + streptozotocin (35 mg/kg; i.p) in male Wistar rats pretreated with or without PCA (15 or 30 mg/kg for 6 d).Results PCA at 15 and 30 mg/kg significantly upregulated the levels of body weight (BW; 230.2, 257.8 g), high density lipids (22.68, 34.78 mg/dL), glutathione (10.24, 16.21 nmol/mg), superoxide dismutase (21.62, 29.34 U/mg), glucagon-like peptide-1, glucose transporter-4, Wnt1, and β-catenin, while downregulating those of liver weight (LW; 9.4, 6.7 g), BW/LW (4.1, 2.6%), serum glucose (165, 120 mg/dL), serum insulin (13.46, 8.67 μIU/mL), homeostatic model assessment of insulin resistance (5.48, 2.57), total cholesterol (68.52, 54.31 mg/dL), triglycerides (72.15, 59.64 mg/dL), low density lipids (42.18, 30.71), aspartate aminotransferase (54.34 and 38.68 U/L), alanine aminotransferase (42.87, 29.98 U/L), alkaline phosphatase (210.16, 126.47 U/L), malondialdehyde (16.52, 10.35), pro-inflammatory markers (tumor necrosis factor α (TNF-α (149.67, 120.33 pg/mg)) , IL-6 (89.79, 73.69 pg/mg) and IL-1β (49.67, 38.73 pg/mg)), nuclear factor kappa B (NF-κB), and interleukin-1β, and ameliorated the abnormal pathological changes in IR/D rats.Discussion and conclusion PCA mitigates the IR, lipid accumulation, oxidative stress, and inflammation in liver tissues of IR/D rats by modulating the NF-κB and Wnt1/β-catenin pathways.